Sistim Penyajian Keuangan Pesantren Darul Hikmah, Banten - Achmad Fauzi; Amor Marunda; Faroman Syarif; Raden Achmad Harianto (Jurnal Portofolio : Jurnal Manajemen dan Bisnis, 2022)
Without good management and financial reports, it can be said that the boarding school has not been said to be successful in its management. One of the sources that support the success of Islamic boarding schools in carrying out development is finance, because the financial sector is a supporter in the management of education. For this reason, good and transparent financial management is needed, so that the weaknesses and shortcomings of Islamic boarding schools can be known by other interested parties. The financial statements of Islamic boarding schools only present reports of cash receipts and disbursements, which are not in accordance with the classification of items in accordance with applicable financial accounting standards because the foundation does not recognize the accounting standards used as financial reporting guidelines for non-profit entities. Methods of community service activities This method uses lectures or counseling, discussion and learning methods that are practiced by participants and resource persons. The lecture method is used to convey general knowledge about the financial statements of Islamic boarding schools, SAK ETAP, SAK 45 and SAK Syariah accompanied by a question and answer session. Learning methods are used to transfer knowledge or skills and value systems possessed by resource persons to community members